2008
DOI: 10.1038/nmat2160
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic electrochemistry at insulators

Abstract: The identity of charges generated by contact electrification on dielectrics has remained unknown for centuries and the precise determination of the charge density is also a long-standing challenge. Here, electrostatic charges on Teflon (polytetrafluoroethylene) produced by rubbing with Lucite (polymethylmethacrylate) were directly identified as electrons rather than ions by electrochemical (redox) experiments with charged Teflon used as a single electrode in solution causing various chemical reactions: pH incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
236
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(251 citation statements)
references
References 21 publications
13
236
0
2
Order By: Relevance
“…32,33 The chemical reactions have been explained to be induced by a surplus of electrons at the polymer surface, produced by the rubbing. While weakly bound electrons may be capable of inducing redox reactions, ions are not.…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…32,33 The chemical reactions have been explained to be induced by a surplus of electrons at the polymer surface, produced by the rubbing. While weakly bound electrons may be capable of inducing redox reactions, ions are not.…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…As is known, the redox reactions are the signature for electron transfer because it leads to the valence change. Therefore, many experiments depend on the redox reactions to indicate the dominant charge transfer process [45,46]. In turn, dependent on these experiments, the electro-potential of the surface (compared to H+/H 2 (0 V versus NHE), which is not necessarily equal to the electro-potential energy) can be more quantitatively determined [46].…”
Section: Ionmentioning
confidence: 99%
“…When two polymers like Teflon and Lucite were rubbed together vigorously, it was found by Liu and Bard [33][34][35] and by Otero 36 that the surface charges developed can carry out different chemical redox reactions such as metal deposition, ion reduction and chemiluminescence, reactions which can be induced by electrons but not by ions. This conclusion was later challenged by Piperno et al 37 because it was shown that rubbing of these polymers results in transfer of material containing polar active species so that the surfaces are charged by ions.…”
Section: The Case For Electron Exchangementioning
confidence: 99%
“…The term rubbing contacts has been used in many publications on contact charging without any further definition, and the term vigorous rubbing is sometimes used. [33][34][35][36] In this review, pressing is defined as applying pressure during contact with no intent of applying friction. For example, in the report by Baytekin et al,4 it states: "the pressure applied during contact.…”
Section: Effect Of the Nature Of The Contactsmentioning
confidence: 99%